Public Sector CSR Communication: A Dialogical Approach - Thomsen, Christa (HERMES - Journal of Language and Communication in Business, 2007)
Public sector organisations have different communication needs from private sector organisations. For example, they quite often have programmes aimed at behaviour changes, challenging their ability to choose the strategy which best suit their purpose. Dialogue is often considered a strategic tool which can lead to organisational gains such as motivation, learning, development, collaboration, etc. This article examines the role of dialogue in Danish public sector Corporate Social Responsibility (CSR) Communication aimed at behaviour change and employer mobilisation. The focus is on central government CSR communication strategies and how these strategies are implemented by a local government. It is argued that public actors’ (government departments, State agencies and local bodies) communication with employers on CSR is behaviour change communication and that it is possible to analyse this communication within the framework of a dialogue analysis model developed in linguistics. A theoretical dialogue-change model is proposed as an alternative to how government departments, State agencies and local bodies can mobilize employers.